A STUDY OF THE POTENTIATING EFFECT OF TOPICAL PROPARACAINE 0.5% ON TROPICAMIDE 0.8% AND PHENYLEPHRENE 5% INDUCED MYDRIASIS IN A SOUTHINDIAN POPULATION - CHELLAKUMAR, VIKRAM; RAVINDRAN, DHARSHINI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Pupillary dilatation is an integral part of comprehensive ophthalmic examination. It is also essential for cataract surgery and outpatient laser procedures. Rapid and sustained dilatation is often required. It has been proposed that prior instillation of proparacaine 0.5% can potentiate the effect of the routinely used tropicamide 0.8% phenylephrine 5% combination mydriatic agent. However, certain studies have shown that it is not effective in dark colored iris as compared to light colored iris; hence, this study was done on a predominantly South Indian population with dark iris. Methods: Hundred eyes of 50 patients requiring pupillary dilatation as part of routine ophthalmic evaluation were included in the study. The patients were divided into two groups. The study group was given 0.5% proparacaine before instillation of mydriatic agent and the control group was given only tropicamide 0.8% and phenylephrine 5% eye drops. Pupillary dilatation was measured after 15 min and 30 min in both eyes. The end point was taken as 6 mm pupillary dilatation. Results: There was a statistically significant difference in the rate of pupillary dilatation between the control and the study group at 15 min and 30 min after instillation of eye drops. Conclusion: The study concluded that prior instillation produced faster dilatation even in patients with dark colored iris; hence, we suggest the use of topical anesthetic proparacaine 0.5% in situations where rapid mydriasis is required.